Female anoles retain responsiveness to testosterone despite the evolution of androgen‐mediated sexual dimorphism. (23rd December 2014) - Cox, Christian L.; Hanninen, Amanda F.; Reedy, Aaron M.; Cox, Robert M.
Summary: The evolution of sexual dimorphism presents a challenge because males and females must express two phenotypes from the same underlying genome. In vertebrates, one solution to this challenge is to link the expression of shared traits to sex steroids. However, even 'male‐biased' steroids such as testosterone (T) circulate at biologically significant levels in females, raising the question of whether sexual dimorphism evolves not only through the coupling of trait expression to T in males, but also through the decoupling of trait expression from T in females. We tested these alternatives by asking whether male and female brown anoles ( Anolis sagrei ) respond to exogenous T in similar fashion with respect to a suite of sexually dimorphic traits: growth, skeletal morphology, resting metabolism, fat storage, dewlap size and dewlap colour. First, we established the ontogeny of sexual dimorphism in a colony raised in a laboratory common garden. Next, we treated juveniles of each sex with either T implants or empty implants at 5–8 months of age, when sexual dimorphism first began to develop for most traits. T stimulated growth in both sexes and largely abolished natural sex differences in growth. This effect was associated with the stimulation of resting metabolism and the diversion of energy from fat and liver stores in both sexes. T also enlarged the dewlap in both sexes, though females never developed dewlaps equal in size to those of males. Finally, T altered the brightness and saturation of the dewlap in both sexes, inducing coloration similar to that of adult males. Female brown anoles retain many of the same tissue‐specific responses to T that occur in males, suggesting that the evolution of androgen‐mediated sexual dimorphism has been achieved largely through the coupling of trait expression to sex differences in circulating T, without an associated decoupling of trait expression from T in females. Abstract : Lay Summary